High‐Resolution Printing of 3D Structures Using an Electrohydrodynamic Inkjet with Multiple Functional Inks. (19th June 2015) - An, Byeong Wan; Kim, Kukjoo; Lee, Heejoo; Kim, So‐Yun; Shim, Yulhui; Lee, Dae‐Young; Song, Jun Yeob; Park, Jang‐Ung
<x xml:space="preserve">Abstract</x> Electrohydrodynamic‐inkjet‐printed high‐resolution complex 3D structures with multiple functional inks are demonstrated. Printed 3D structures can have a variety of fine patterns, such as vertical or helix‐shaped pillars and straight or rounded walls, with high aspect ratios (greater than ≈50) and narrow diameters (≈0.7 μm). Furthermore, the formation of freestanding, bridge‐like Ag wire structures on plastic substrates suggests substantial potentials as high‐precision, flexible 3D interconnects.